Juvenile Miranda warnings: perfunctory rituals or procedural safeguards? - Rogers, Richard (Criminal justice and behavior, 2012)
The American Bar Association, via its newly adopted policy, seeks fundamental changes in procedural justice with respect to juvenile Miranda warnings. It calls for understandable Miranda warnings to educate youth in custody regarding the relevant Constitutional protections. In surveying prosecutors and public defenders, the authors collected 293 juvenile Miranda warnings that are intended specifically for youthful offenders. Length and reading levels were analyzed and compared to an earlier survey. Nearly two thirds (64.9%) of these warnings were very long (> 175 words), which hinders Miranda comprehension. In addition, most juvenile warnings (91.6%) require reading comprehension higher than a 6th-grade level; 5.2% exceed a 12th-grade reading level. Combining across two surveys, more than half of juvenile Miranda warnings are highly problematic because of excessive lengths or difficult reading comprehension. However, simple and easily read Miranda components were identified that could be used to improve juvenile advisements. Breaking new ground, Miranda waivers were examined for both juveniles and their parents/interested adults. Interestingly, most juvenile versions emphasized waivers in positive terms (e.g., "an opportunity") and downplayed the potential for negative consequences.